THE TETHYAN OCEANIC GATES: A TECTONIC APPROACH TO MAJOR SEDIMENTARY CHANGES WITHIN TETHYS - Ricou L.E. (My University, 1987)
Accepting that the opening or closure of seaways has consequences on the oceanic circulation which in turn influences sedimentation, major changes in Tethyan geometry are checked against major changes in sedimentation. Time relationships can be demonstrated between the two group of phenomena and causal links are discussed. As the causes for major sedimentary changes are numerous and their respective roles controversial, it is speculated if the observed change in geometry could have had a positive effect on the associated change in sediments. Ever since the birth of the Mesozoic Tethys which formed from the break-up of Pangea till its death through multiple collisions, this ocean played a major role in the world ocean circulation, being the sub-equatorial seaway which permitted a circumterrestrial circulation at low latitudes. Five successive steps, separated by four major changes, are recognized : i) during the Trias and the Jurassic, the young Tethys was a triangular cul-de-sac expanding westward through distensive tectonics and subsidence, and influenced along its southern margin by a westward current and associated upwelling; radiolarites take a growing part in its sedimentation; ii) during the Tithonian, radiolarites were abruptly replaced by pelagic limestones (Majolica) in many places and the corresponding CCD drop is tentatively correlated with the full opening of the Tethyan seaway which reached the Pacific Ocean through the Caribbean and with the corresponding reorganization of currents; iii) during the Early Cretaceous, Apulia began its collision with the precursor elements of the European margin, thus hindering deep water exchange; this pre collision favoured the mid Cretaceous anoxia with affected sedimentation in numerous basins; iv) during the Late Cretaceous, repeated distension and subsidence (since the Aptian) between Apulia and Africa gave a growing importance to the south Apulian seaway; this new opportunity of water exchange favoured the end of anoxia and the deposition of new pelagic limestones (scaglia); as a matter of fact, the location of the Late Cretaceous to Early Eocene phosphorites testify to a well-established westward current along this south-Apulian seaway; v) the late Eocene to Oligocene general collision was responsable for the death of this current and the corresponding breakdown of the Tethyan seaway into independent groups of basins.
Keywords: Eocene; Jurassic; Oligocene; Tithonian; Aptian; Mesozoic; Cretaceous; Mesozoic::Jurassic::Upper::Tithonian; Мезозой::Меловая; Mesozoic::Cretaceous::Lower::Aptian; Кайнозой::Палеоген::Олигоцен; Mesozoic; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Eocene; Мезозой::Юрская; Мезозой::Юрская::Верхний::Титонский; Mesozoic::Jurassic; Мезозой::Меловая::Нижний::Аптский; Cenozoic::Paleogene::Oligocene; Mesozoic::Cretaceous; Мезозой